Applying a Verification Protocol to Evaluate the Accuracy of Functional Size Measurement Procedures: An Empirical Approach - Quesada López, Christian Ulises (2016)
This paper presents a verification protocol for analyzing the source of inaccuracy in measurement activities of Function Points Analysis (FPA) and Automated Function Point (AFP). An empirical study was conducted with the protocol to determine the accuracy of FPA and AFP, and common differences during their application. The empirical study was conducted and differences between the measurement process regarding accuracy, reproducibility, and protocol adoption properties were reported. Effectiveness of the verification protocol to evaluate functional size measurement procedures was provided. The application of the protocol enabled participants to identify differences and their causes between counting results in a systematic way. Many participants had a favorable opinion regarding the usefulness of the protocol, and most of them agreed that the application of this protocol improved their understanding of measurement methods.